The composition of algae in the Lake Arakhley during spring-summer period (Transbaikal region) - N. A. Tashlykova (Acta Biologica Sibirica, 2019)
According to the materials of hydrobiological examination of the Lake Arakhley spring and summer 2017 are presented: taxonomic structure, a list of identified microalgae, as well as the composition of the dominant complex. It is established that phytoplankton of the lake has 97 taxa below the genus. Its basis (86.6%) is made up of representatives of four phyla: Bacillariophyta, Chlorophyta, Chrysophyta and Cyanobacteria. The most commonly encountered species were: Lindavia comta, Fragilaria crotonensis, F. radians, Ulnaria ulna, Cocconeis placentula, Nitzschia graciliformis, Chrysococcus rufescens, Dinobryon cylindricum, D. divergens, D. sertularia, Kephyrion spirale, Oocystis marssonii.